2017
DOI: 10.7759/cureus.1061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Interventional Management of Pain After Vertebral Augmentation Procedures

Abstract: IntroductionA small subset of patients who underwent successful vertebral compression fracture (VCF) augmentation procedures may develop subsequent pain requiring spinal injections. In a retrospective analysis, we determined whether the pain was related to the original fracture site or to another area within the lumbar or thoracic spine. The pain occurred either at the same/adjacent level and/or non-adjacent level as the VCF. Interventional treatments primarily targeted the facet joints, specifically in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…Dual or triple array epidural leads have been used to provide stronger axial coverage [ 19 , 20 ]. This may be important in patients with more diffuse lumbar pain associated with multiple vertebral compression fractures [ 11 - 13 ]. Another option is a combination of an epidural lead with a second lead positioned in the lumbar subcutaneous tissue for peripheral nerve field stimulation (PNFS) [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual or triple array epidural leads have been used to provide stronger axial coverage [ 19 , 20 ]. This may be important in patients with more diffuse lumbar pain associated with multiple vertebral compression fractures [ 11 - 13 ]. Another option is a combination of an epidural lead with a second lead positioned in the lumbar subcutaneous tissue for peripheral nerve field stimulation (PNFS) [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some degree of persistent pain after vertebral augmentation and kyphoplasties is common especially when the fractures are in the lumbar spine [ 11 , 12 ]. Back pain persisting after the first three months post vertebroplasty is seen in 19% to 23% of cases [ 13 ]. Radicular pain is not usually associated with osteoporotic vertebral compression fractures, however, these elderly patients may also have chronic extremity pain from peripheral neuropathy or from other osteoporotic fractures in the hip or after joint replacement that can be helped with spinal cord stimulation targeting both the lumbar spine and lower extremities [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Persistent pain after a vertebral augmentation can be caused by different spinal problems, including another osteoporotic compression fracture at a new or adjacent level, surgical infection, concurrent lumbar stenosis, and rarely, a recurrent fracture at the previously treated level [ 11 , 15 ]. There are case reports of the development of an adjacent level fracture as early as the first month after kyphoplasty [ 3 , 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…As the population becomes older, it is common to see patients developing concurrent spinal problems such as lumbar spinal stenosis (LSS), degenerative spondylolisthesis (DSL), and osteoporotic vertebral compression fractures (VCF). These conditions often affect the same or adjacent regions of the thoracic and lumbar spine [ 1 - 3 ]. Large radiologic and anatomic studies have shown a biphasic distribution of VCF with 45% to 55% found in the mid-thoracic spine from T6 to T8, and 10% to 20% from T12 to L2 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) and computerized tomography (CT) scans are a key part of the diagnosis. Often patients are being studied for one problem, such as a traumatic VCF, and are found to have previously asymptomatic lumbar stenosis or spondylolisthesis; or the reverse, where a patient is being evaluated for radicular pain or neurogenic claudication, and is found to have a previous VCF [ 3 , 5 ] (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%